Arginase activity and nitric oxide levels in patients with obstructive sleep apnea syndrome - Pelin, Zerrin; Yuksel, Meral; Okur, Hacer Kuzu; Ogunc, Ayliz Velioglu; Ozturk, Levent (HOSPITAL CLINICAS, 2014)
OBJECTIVE: Obstructive sleep apnea syndrome is characterized by repetitive obstruction of the upper airways, and it is a risk factor for cardiovascular diseases. There have been several studies demonstrating low levels of nitric oxide in patients with obstructive sleep apnea syndrome compared with healthy controls. In this study, we hypothesized that reduced nitric oxide levels would result in high arginase activity. Arginase reacts with L-arginine and produces urea and L-ornithine, whereas L-arginine is a substrate for nitric oxide synthase, which produces nitric oxide. METHODS: The study group consisted of 51 obstructive sleep apnea syndrome patients (M/F: 43/8; mean age 49 +/- 10 years of age) and 15 healthy control subjects (M/F: 13/3; mean age 46 +/- 14 years of age). Obstructive sleep apnea syndrome patients were divided into two subgroups based on the presence or absence of cardiovascular disease. Nitric oxide levels and arginase activity were measured via an enzyme-linked immunosorbent assay of serum samples. RESULTS: Serum nitric oxide levels in the control subjects were higher than in the obstructive sleep apnea patients with and without cardiovascular diseases (p<0.05). Arginase activity was significantly higher (p<0.01) in obstructive sleep apnea syndrome patients without cardiovascular diseases compared with the control group. Obstructive sleep apnea syndrome patients with cardiovascular diseases had higher arginase activity than the controls (p<0.001) and the obstructive sleep apnea syndrome patients without cardiovascular diseases (p<0.05). CONCLUSION: Low nitric oxide levels are associated with high arginase activity. The mechanism of nitric oxide depletion in sleep apnea patients suggests that increased arginase activity might reduce the substrate availability of nitric oxide synthase and thus could reduce nitric oxide levels.
Keywords: Obstructive Sleep Apnea Syndrome; Nitric Oxide; Arginase Activity; Cardiovascular Diseases